A STUDY OF SEDIMENT DELIVERY RATIO USING AVSWAT-X IN THE CATCHMENT AREA OF PACAL RESERVOIR OF BOJONEGORO - Zulis Erwanto; Nadjadji Anwar; Bambang Sarwono (Institut Teknologi Sepuluh Nopember, 2010)
Recently, the flood intensity that brought by tributary rivers in the catchment area of Pacal reservoir has increased, both in the quantity of runoff and sediment volume. The research aims to set up erosion rate modeling and find the formulation of the Sediment Delivery Ratio (SDR) at Pacal reservoir. The research used USLE and MUSLE methods as comparator to find sediment yield accuracy at Pacal reservoir, by applying ArcView SWAT-X software. Total average annual erosion rate in the catchment area of Pacal reservoir which has area 82 Km2 calculated using USLE and MUSLE methods are 159,31 ton/ha/yr and 582 ton/ha/yr respectively. MUSLE method resulted SDR which is most closely to SDRobservation if it is compared to USLE method. In this research, MUSLE - Sediment-Discharge Rating Curve method has evaluation values MSE = 0,08; RMSE = 0,29; and Nash = 0,75. Furthermore, Sediment Delivery Ratio at catchment area of Pacal reservoir can be formulated as 0,29 3,83. DAS Waduk Pacal SDR A with value of SDRZulis = 0,27 and sediment yield obtained from MUSLE method equal to 157,40 ton/ha/yr, while from USLE method equal to 43,09 ton/ha/yr. Evaluate sediment yield of MUSLE from SDRZulis to formulation of SDR of former researcher was value of Nash = 0,89; MAE = 0,01. Based on the research result, it is expected that the institution which has responsibility in managing the catchment area of Pacal reservoir would pay high attention to zonation map of erosion risk level and can overcome sedimentation in Pacal reservoir.